A scoping review of dialogic formative feedback practices in higher education - Nedrehagen, Eirik; Vee, Tove Sandvoll; Stokstad, Janette Moland; Orm, Stian (Frontiers in Education, 2025)
BackgroundFeedback practices in higher education are important for student learning and engagement, and unfortunately, both students and university teachers report being dissatisfied with existing feedback practices. Existing practices are often summative instead of formative, and it has been proposed that the use of formative feedback can enhance learning and student satisfaction in higher education. This preregistered scoping review (https://doi.org/10.17605/OSF.IO/2J4M5) aimed to map the current literature on dialogic formative feedback in higher education and provide an overview of the various approaches to dialogic formative feedback and the evaluation of outcomes of these practices as reported in the literature.MethodThe review followed established methodological frameworks for scoping reviews and report according to the PRISMA Extensions for Scoping Reviews (PRISMA-ScR): Checklist and Explanation. We searched ERIC, Scopus, CINAHL, the Teacher Reference Center, and sources of gray literature to identify relevant studies. The search strategy was developed in collaboration with a research librarian, who conducted the final search. Two independent reviewers screened all identified records against predefined inclusion criteria.ResultsA total of 40 sources met the inclusion criteria. The studies varied considerably in terms of the purpose, setting, and content. However, most records described aims related to cognitive growth and increased self-regulated learning. Feedback was delivered across diverse contexts, most commonly in small group settings. The records identified several students-and teacher-related factors that appeared to influence the learning outcomes of formative feedback. Most of the sources focused on cognitive and affective measures (n = 11) or students’ experiences and perceptions (n = 10), while comparatively fewer examined teacher experiences and perceptions (n = 2) or academic achievement outcomes (n = 5).ConclusionThe findings suggest that dialogic formative feedback can be implemented in a wide range of higher education contexts to promote self-regulated learning and cognitive development. Future research should investigate its effectiveness in improving academic achievement and further explore the impact of dialogic formative feedback on students’ educational outcomes, as well as teachers’ perspectives on applying dialogic feedback practices.